Forced Duction Test: Is It Necessary after the Scleral Buckling Procedure? - Mohammad Sharifi; Mohammad Reza Ansari Astaneh (Case Reports in Ophthalmology, 2020)
A 14-year-old boy who had ocular motility disorder which started 2 weeks following retinal surgery (scleral buckling) secondary to rhegmatogenous retinal detachment, was referred to the strabismus clinic. He had significant ocular movement limitations in adduction and elevation under general anesthesia. The forced duction test (FDT) was positive in both adduction and elevation. After buckle removal, FDT was negative. The eye was orthotropic without ocular movement limitation at final follow-up. In conclusion, FDT at the end of the scleral buckling procedure needs to be performed. It may prevent restrictive strabismus after scleral buckling surgery.